Editorial introduction: Advances in theory and practice of digital marketing. (March 2020) - Dwivedi, Yogesh K.; Rana, Nripendra P.; Slade, Emma L.; Singh, Nitish; Kizgin, Hatice
Abstract: This special issue of the Journal of Retailing and Consumer Services aims to bring together a variety of disciplines and a scholarly community for the advancement of knowledge regarding practice and research related to digital and social media marketing. Accordingly, the special issue includes papers using a variety of theories, research methods, contexts, and conceptualizations to enrich our understanding of digital and social media marketing from consumer and practitioner perspectives. The thirteen articles accepted for inclusion in this special issue are summarised in this editorial introduction.